COMUNIDAD DE INSECTOS CAPTURADOS EN TRAMPAS DE INTERCEPCIÓN (PITFALL TRAPS) EN UNA RESERVA DEL CHACO SEMIÁRIDO EN EL CENTRO DE ARGENTINA - Molina, S. I.; Valladares, G. R.; Gardner, S.; Cabido, M. R. (Acta Entomológica Chilena, 2022)
The ground -dwelling insect community was studied in a Natural Reserve of semiarid Chaco Forest, in Central Argentina. Five collections were made between MarchI992- December 1993, each consisting of 60 randomly placed pitfall traps. Coleóptera and Díptera were the most important orders, in terms of both family richness and number of individuáis. The species composition of Coleóptera was analyzed, Tenebrionidae being the most diverse and abundant family, while Carabidae was remarkably poor. The trophic structure of the system was dominated by scavengers. These represented the richest and most abundant feeding guild, for the insect community in general and for Coleóptera in particular.